Semiconductor quantum dots for photodynamic therapy: Recent advances - Uprety, Bhawna; Abrahamse, Heidi (Frontiers in Chemistry, 2022)
Photodynamic therapy is a promising cancer treatment that induces apoptosis as a result of the interactions between light and a photosensitizing drug. Lately, the emergence of biocompatible nanoparticles has revolutionized the prospects of photodynamic therapy (PDT) in clinical trials. Consequently, a lot of research is now being focused on developing non-toxic, biocompatible nanoparticle-based photosensitizers for effective cancer treatments using PDT. In this regard, semiconducting quantum dots have shown encouraging results. Quantum dots are artificial semiconducting nanocrystal with distinct chemical and physical properties. Their optical properties can be fine-tuned by varying their size, which usually ranges from 1–10 nm. They present many advantages over conventional photosensitizers, mainly their emission properties can be manipulated within the near IR region as opposed to the visible region by the former. Consequently, low intensity light can be used to penetrate deeper tissues owing to low scattering in the near IR region. Recently, successful reports on imaging and PDT of cancer using carbon (carbon, graphene based) and metallic (Cd based) based quantum dots are promising. This review aims to summarize the development and the status quo of quantum dots for cancer treatment.